Effectiveness of Modified Scapular Exercise and Stretching Exercise on Pressure Pain and Neck Disability in Architecture Students with Mechanical Neck Pain in Denpasar - Aryaning Dwi Antyesti; Nila Wahyuni; Wahyuddin; Dewa Putu Gede Purwa Samatra; Luh Putu Ratna Sundari; Ni Wayan Tianing (PT Inovasi Pratama Internasional, 2023)
This study aimed to prove the difference in the effectiveness of modified scapular exercise compared to stretching exercise in pressure pain and neck disability in architecture students with mechanical neck pain in Denpasar. This research is experimental research with pre and post-test two-group design. The research sample consisted of 16 people who were divided into two groups by simple random sampling. Group 1 with the modified scapular exercise intervention and group 2 with the stretching exercise intervention. Both groups received treatment 3 times a week for 6 weeks. Measurements were made before and after treatment. Pressure pain was measured with a pressure algometer and neck disability were measured with the Indonesian version of the neck disability index questionnaire. Based on the paired sample t-test on modified scapular exercise and stretching exercise, the results obtained were right and left pressure pain with a value of p<0.001 and neck disability with p<0.001, which means that there was a significant difference in the decrease of pressure pain and neck disability before and after the intervention, in each group. For the independent sample t-test, the value of right pressure pain was p<0.05, left pressure pain was p<0.05, and neck disability was p<0.001, which showed significant differences in the decrease of pressure pain and neck disability in the two groups. In conclusion, modified scapular and stretching exercises can decrease pressure pain and neck disability in architecture students with mechanical neck pain in Denpasar. However, based on the analysis of the results of the intervention, modified scapular exercise was more effective in decreasing pressure pain and neck disability in architecture students with mechanical neck pain compared to stretching exercise.